Pilihan Politik Masyarakat Melayu Pesisir Pantai di Kecamatan Tanjung Tiram Kabupaten Batu Bara Tahun 2019 - Doni, Muhammad Rahma (Jurnal Hukum dan Demokrasi (JHD), 2024)
Political choices are preferences, actions, and individual information processing to make political decisions. Although it is often assumed that political institutions play a major role in public policy making, individuals also have the ability to influence political institutions. Community participation in politics is when an individual or a group of people actively engage in political life, including in the election of national leaders, and directly or indirectly influence government policies, public policy. This research uses a qualitative method (Field Research) that is descriptive by using primary data sources, conducting interviews with the coastal Malay community of Tanjung Tiram, community leaders, Malay Youth, Head of the Batu Bara KPU, and Religious Leaders, regarding the political choices of the Tanjung Tiram coastal community in Batu Bara Regency, the political insights of the coastal Malay community, and the cultural impact of Malay culture on the political choices of the community.